(untitled) (AYUSHDHARA, 2025)
Chronic inflammatory and hyperproliferative skin disease caused by the immune system called psoriasis. It typically follows a relapsing and remitting course and is distinguished by well-defined, erythematous, scaly plaques that typically affect the extensor surfaces of the face, head, and extremities. Nearly 0.44% to 2.8% of people worldwide suffer with psoriasis. A form of Kshudra Kushta, Eka Kushta has Vata-Kapha predominance and a clinical appearance similar to psoriasis. Numerous therapies have been documented in Ayurveda, including Shodhana and Shamana. A male patient, aged 57 years, developed erythematous plaques on the extensor surfaces of both upper limbs. In accordance with Ayurvedic Samprapti (pathophysiology), Virechana followed by Shamanoushadi, which includes Dushivishari Gulika 1 Vati twice a day, Manjishtadi Kwath 40ml twice a day on an empty stomach, Kaishore Guggulu 2 Vati twice a day after meals, 500mg of Arogyavardhini Rasa and 2gm of Triphala Churna with Anupana of Koshna Jala was administered. The patient experienced total symptom alleviation after four months of treatment. Photographic documentation was taken during treatment with the patient’s consent. There is significant improvement from persistent cases of psoriasis when a healthy diet and Ayurvedic treatment are followed.